Peran dan Fungsi Dog Meat Free Indonesia (DMFI) dalam Menangani Kasus Perdagangan Daging Anjing di Indonesia - Maya, Herzalia; Pattipeilohy, Shary Charlotte Henriette (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Indonesia has become an international spotlight due to the massive and brutal trade and consumption of dog meat in several regions in Indonesia. Therefore, Indonesian government chose to cooperate with Dog Meat Free Indonesia (DMFI) coalition which was formed of some international animal protection organizations, which are: Humane Society International, Animals Asia, and the Change for Animal Foundation. This study seeks to analyze roles and functions of DMFI and the objectives of Indonesian government in its cooperation with DMFI. Theories used in this research is theory of role and function of international organizations and the theory of neoliberal institutionalism. The role of DMFI as an international organization is as an actor, and its functions are articulation and aggregation, rule-making, information, and operation. This study, if analyzed using the theory of neoliberal institutionalism, found that Indonesia's goal of collaborating with DMFI was to get maximum results to solve the problem of the dog meat trade. In addition, DMFI can provide information to Indonesia regarding the behavior of other countries in the issue of the dog meat trade